2019
DOI: 10.13057/biodiv/d200912
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of pollen features and peroxidase isozymes in their morphological complexity of ten local cultivars of sweet potato from Indonesia

Abstract: Abstract. Suranto, Wahyuni D, Edy Purwanto E. 2019. Evidence of pollen features and peroxidase isozymes in their morphological complexity of ten local cultivars of sweet potato from Indonesia. Biodiversitas 20: 2511-2518. Sweet potato (Ipomoea batatas Lam) has been recorded to have many cultivars and variations in the morphological characters not only for the leaves but also for the tubers. Sweet potatoes had economically significant role, especially as an additional food due to its high content of carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…The differences between isozyme banding patterns can be interpreted as revealing the genetic diversity between varieties of plants (Suratman et al 2016). A related finding was also reported by Suranto et al (2019) in 10 cultivars of sweet potato using peroxidase isozymes. Accordingly, Restykania et al (2019) also found isozyme variation among madeira vine (Anredera cordifolia).…”
Section: Discussionsupporting
confidence: 66%
“…The differences between isozyme banding patterns can be interpreted as revealing the genetic diversity between varieties of plants (Suratman et al 2016). A related finding was also reported by Suranto et al (2019) in 10 cultivars of sweet potato using peroxidase isozymes. Accordingly, Restykania et al (2019) also found isozyme variation among madeira vine (Anredera cordifolia).…”
Section: Discussionsupporting
confidence: 66%
“…Perbedaan ornamen ini disebabkan karena kedua macam tanaman ini berbeda spesies. Hal ini juga dijelaskan oleh Agashe & Caulton (2009) dan Edtman (1952), dan juga dikonfirmasi oleh Purnobasuki, Etik, & Thin (2014), Suranto, Wahyuni, & Purwanto (2019) dimana bentuk fitur polen dalam satu spesies biasanya memiliki sifat yang sama.…”
Section: Metodeunclassified